Abundance of golden apple snail (Pomacea canaliculata) in paddy field using difference trapping method / Nuryang Suhaida Samsudin - Samsudin, Nuryang Suhaida (Faculty of Plantation and Agrotechnology, 2016)
The golden apple snail (GAS) Pomacea canaliculata from Ampullaridae family is one of the large freshwater snails from tropical to subtropical South America. The GAS become important major pests in the paddy rice in Malaysia that affect the yield of production. The main focus of this study to know the abundance of. The GAS on this field and a field researched was conducted at Van, Kedah for five weeks by using two different trapping method which is using jackfruit's skin and stick wood. From the SPSS analyzed the data was not normally distributed (P < 0.05) while the Kruska1 - Wallis Test show that the Golden Apple Snail was not significant (x2 = 10.916 ; df = 9 ; P> 0.05). Supported by t- test the data is significant because even using different trap the data not shown too much changes. The GAS abundance had significant with the climatic factor. The mean of GAS for jackfruit's skin the lowest was on loth collection and the highest is on the 4th collection while for the stick wood the lowest mean was 2nd collection and the highest was on the 5th collection.